A time-motion, technical and tactical analysis of lightweight women's judo - Challis, D. G. (2017)
Introduction: This study analysed lightweight women`s judo from three common aspects, time-motion, technical and tactical in order to develop a deeper understanding of the demands placed specifically on this population and whether they differ to others. This information may allow coaches to develop specific training for this population. Method: Analysing all the fights that included lightweight women in the 2010 and 2014 World Judo Championships, 251 athletes across 267 contests were analysed. Video was collected live and downloaded from youtube before being analysed in Sportscode Elite software and exported into Microsoft excel and SPSS for further analysis. Results: Lightweight women appear to have similar time-motion characteristics to previous research across all weight categories. Of the 2284 attacks Ippon-seoi-nage, Uchimata and Sode-tsuri-komi-goshi have the highest frequency but the most efficient throws are O-sotogari, Morote-seoi-nage and O-uchi-gari. The most prevalent and efficient category for Tachiwaza techniques was Ashi-waza and in Ne-waza it was Osaekomi-waza. The effects of laterality and handedness seen in previous research either does not apply to this population or its affects have diminished across judo. Discussion and conclusion: There are similarities between previous reports across weight categories and lightweight women`s judo for time-motion characteristics, types of technique used, category of techniques used, direction of attack, laterality and use of combinations. However, differences appear in the efficiency of counters with lightweight females being very effective at countering their opponents. The popularity of Sode-tsuri-komi-goshi should be closely considered by coaches and is likely to be an emerging theme across all weight categories. There is also significant difference in the data analysing the effect of laterality on performance with difference seeming to diminish, this may also be an emerging trend across all weight categories and possibly all sports. This research appears to be one of the first to tackle fatigue based upon elite level performance in judo and the first to categorise Shido`s by the offence and shows the larger number of offences are for passivity. There are also large discrepancies noted between this research and the IJF databases.